Análisis comparativo de los frameworks híbridos y nativos en el desarrollo de apps para móviles Android. - Jiménez Anastacio, David Bolívar (2022)
After a detailed investigation proposed by the comparative analysis of hybrid and native frameworks in the development of apps for android mobiles, it is of vital importance to know with which of the two types of frameworks to be able to work as a user, it has been possible to determine that according to the version of the users who have been surveyed make it known that it is better to work or use hybrid frameworks, however, through the collection of data that has been found and the bibliography that has been searched, the respective comparative analysis was carried out where it was possible to show that It is much more recommended to use a native framework in the development of mobile apps in android. Since the advantages that native frameworks have as opposed to hybrid frameworks can be detailed in a very clear way and therefore the improvements that native frameworks bring with them as opposed to hybrid frameworks can be highlighted, it is convenient to be able to use a type of framework that is faster and easier to use when developing a mobile app for android, and therefore have control of what is being done so that the user has a higher quality experience when using or disposing of their mobile. However, we cannot fail to mention that a hybrid framework is also very important and is very good when developing an app for Android mobiles, but the native framework stands out for the greater capacity that it has, unlike the other, it is for this reason, the users surveyed refer to the fact that the hybrid framework is better, however, through the comparative analysis that has been done, the best is a native framework.